Iran nuclear accord and the remaking of the Middle East - Entessar, Nader; Afrasiabi, Kaveh L. (Rowman & Littlefield, 2018)
This book focuses on the final nuclear agreement between Iran and the 5+1 great powers, the ensuing debates around it, and its global and regional ramifications especially in the Middle East. The first section analyzes the agreement through the prism of international relations theories, using a constructivist-critical theory approach. This is followed by an overview of the intense debates in Iran, the West, and other parts of the world, on the nuclear agreement and its various pros and cons, not to mention the connected, yet separate Iran-IAEA agreement. The second section covers Iran's foreign policy and its various priorities, looking in particular at the impact of the nuclear deal on the country's external relations and orientations, contextualized in terms of pre-existing issues and concerns and the profound influence of the nuclear agreement on the perceptions of Iranian power in the region and beyond. The third section then examines the issue of a Middle East nuclear weapons-free zone and the likely consequences of the Iran nuclear deal on this prospect, which, in turn, raises the issue of regional proliferation and counterproliferation. The last section explores some possible various scenarios and the challenges of implementation as a relatively long-term agreement, providing specific policy recommendations for the regional actors and the external powers that are stakeholders in the volatile Middle East.